The Influence of Employees’ Values on the Acquisition of Knowledge in Organizations - Nataša Pivec; Vojko Potočan (Naše gospodarstvo/Our economy, 2015)
In this paper, we focus on the importance and influence of employees’ values as an essential element of organizational culture in the acquisition of knowledge. Based on empirical research, we studied the influence of employees’ values in Slovenian organizations on the acquisition of knowledge, enabling us to identify the core values that exert the greatest effect on the acquisition of knowledge. The results of the analysis confirmed the positive impact of employees’ values on the acquisition of knowledge. We found that the more employees are dedicated to personal development and the more they feel connected and loyal to the organization, the more they are inclined to the development and acquisition of knowledge.